Utilização do alcohol use disorders identification test (Audit) para identificação do consumo de álcool entre estudantes do ensino médio - Martins, Raul Aragão [UNESP]; Manzatto, Antonio José [UNESP]; Da Cruz, Luciana Nogueira [UNESP]; Poiate, Suzy Mary Granzoto [UNESP]; Scarin, Ana Carla Cividanis Furlan [UNESP] (My University, 2008)
Alcohol is one of the drugs most widely used among teenagers. Just recently, studies have been developed regarding the screening of use of alcohol by this population. This work aimed to investigate the use of AUDIT as a method for screening and evaluation of alcohol consumption among High School students. The sample was composed by 1227 students from two public schools, who answered to the Alcohol Use Disorders Identification Test (AUDIT) and informed their socioeconomic level, religion, and occurrence of relationship problems caused by drunkenness of family members. Using an 8 cut-off point, AUDIT has identified 17.8% of students with risk drinking. These results have revealed that AUDIT is easy to be applied and well accepted by the students. It was also evident the importance of this instrument in the follow-up programs of prevention and intervention of alcoholic beverages use.
The use of alcohol use disorders identification test (Audit) to identify alcohol use among high school students
Keywords: Alcohol use; High school; Screening; Teenagers